2009
DOI: 10.1007/s10765-009-0594-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity and Viscosity Measurements of Water-Based TiO2 Nanofluids

Abstract: In this study, the thermal conductivity and viscosity of TiO 2 nanoparticles in deionized water were investigated up to a volume fraction of 3 % of particles. The nanofluid was prepared by dispersing TiO 2 nanoparticles in deionized water by using ultrasonic equipment. The mean diameter of TiO 2 nanoparticles was 21 nm. While the thermal conductivity of nanofluids has been measured in general using conventional techniques such as the transient hot-wire method, this work presents the application of the 3ω metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(133 citation statements)
references
References 35 publications
8
121
1
3
Order By: Relevance
“…Data for the water based nanofluids with SiO2, TiO2 and Al2O3 particles are compared in Fig. 3, 4 with experimental data [15,[34][35][36][37][38][39][40], while the dashed line corresponds to formula (1). Our data are generally in good agreement with data of other authors.…”
Section: Sio2supporting
confidence: 86%
“…Data for the water based nanofluids with SiO2, TiO2 and Al2O3 particles are compared in Fig. 3, 4 with experimental data [15,[34][35][36][37][38][39][40], while the dashed line corresponds to formula (1). Our data are generally in good agreement with data of other authors.…”
Section: Sio2supporting
confidence: 86%
“…Turgut et al [67] prepared TiO 2 nanofluids by enhancing the nanoparticles up to a volume of 3% and observed the relative increase in thermal conductivity and viscosity. They concluded that by varying the volume of nanoparticles, the increase in viscosity was more as compared to the increase in thermal conductivity.…”
Section: Ultrasonication Methodsmentioning
confidence: 99%
“…The viscosity of the nanofluid depends on the quantity and effects of different parameters such as nanoparticle volume fraction [2,67,86,105,107], base fluid, particle size [83], nanolayer thickness, particle shape, dispersion technique, pH value, temperature [66,83,86,105], the effect of clustering and Brownian motion of nanoparticles. Different instruments, like a viscometer, rheometer etc.…”
Section: Viscositymentioning
confidence: 99%
“…They discussed the thermal conductivity of Al2O3,SiO2 and TiO2 [9,31] nanofluid, Al2O3 and CuO [26,32] at a different temperature range from 21 o c and 51 o C. Thermal conductivity was enhanced 2% at 21 o C to 10.8% at 51 o C for same volume concentration of 1%. There was a linear relationship between thermal conductivity ratio and temperature.…”
Section: Temperaturementioning
confidence: 99%